The efficiency of using human potential in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
This article examines the concepts of «human capital» and «human potential». The efficiency of using human potential in the Republic of Kazakhstanwas estimated. The article provides recommendations for increasing theefficiency of using human potential. The effect that human potential has oneconomic growth is examined; national economy performance indicators ofinvestments in human capital are calculated. Also, the theoretical and methodologicalfoundations of human development in market economy conditionsare explored. The influence of human capital on the competitivenessof economic systems has been analyzed. The effectiveness of investmentsin the development of Kazakhstan education has been evaluated. Prioritiesof development of the education system in the Republic of Kazakhstan weredefined. Specific recommendations to improve the quality of the intellectualpotential within the formation of a new educational concept have been given.The method of measuring human potential of society in the present daymarket conditions that allowing analyzing the efficiency of social investmentin education is given. There is the quite clearly influence of the social sphereon development of the economy, which results in a direct relationship ofbasic socio-economic indicators.
Keywords: human potential; human capital; efficiency of using human potential; human development; intelligent production.